(untitled) (Third Sector Social Economic Review, 2011)
This research has been planned and conducted in order to determine nutrition habits, food consumption preferences and the factors effecting these preferences of individuals aged over 45 years old who live in the city of Kilis. Data have been collected from 140 participants by means of a questionnaire. The age of the 64.3 % of the participants is between 45-64, the age of the rest (35.7 %) is 65 and over. 53.6 % of the participants is literate or graduates of primary school. 19.3 % of the individulas do not have any health problems. The health problems encountered frequently by the rest of the participants are: Hypertension, rheumatism, joint complaints, gynecological diseases and stomach sicknesses. It has been detected that 67.0 % of the participants were taking medicene on a regular basis. It has been identified that 40.5 % of the participants aged between 45-64 and 59.5 % of the participants aged over 65 were skipping one meal (p<0.05) and the most skipped meal is lunch. The frequency of rice, pasta and milky dessert consumption is greater in the 65 and over year old age group than the 45-64 year old age group (p<0.05).The beverages consumed most frequently are tea, ayran, milk and Turkish coffee. Besides; it has been determined that celery root, artichoke, broccoli, leek, margarine, salami, sausage and dried garlic beef were generally not preffered because of dislike, lack of eating habit or health problems.